2019
DOI: 10.3390/electronics8121386
|View full text |Cite
|
Sign up to set email alerts
|

Uniform Sampling Methodology to Construct Projection Matrices for Angle-of-Arrival Estimation Applications

Abstract: This manuscript firstly proposes a reduced size, low-complexity Angle of Arrival (AoA) approach, called Reduced Uniform Projection Matrix (RUPM). The RUPM method applies a Uniform Sampling Matrix (USM) criterion to sample certain columns from the obtained covariance matrix in order to efficiently find the directions of the incident signals on an antenna array. The USM methodology is applied to reduce the dependency between the adjacent sampled columns within a covariance matrix; then, the sampled matrix is use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 44 publications
(75 reference statements)
0
5
0
Order By: Relevance
“…. e jβd(M−1)sinθ (7) Here, d represents the separation distance between adjacent elements, and β is the propagation constant. To model the steering vector, which contains the information of elevation angle (i.e., θ) and azimuth angle (i.e., φ), an M 1 × M 2 planar array is supposed to be located in the x-y plane.M 1 and M 2 are the antenna element numbers in the x and y directions, respectively.…”
Section: Adaptive Antenna Array Signal Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…. e jβd(M−1)sinθ (7) Here, d represents the separation distance between adjacent elements, and β is the propagation constant. To model the steering vector, which contains the information of elevation angle (i.e., θ) and azimuth angle (i.e., φ), an M 1 × M 2 planar array is supposed to be located in the x-y plane.M 1 and M 2 are the antenna element numbers in the x and y directions, respectively.…”
Section: Adaptive Antenna Array Signal Modelmentioning
confidence: 99%
“…As a result, MIMO solutions for mm-wave frequencies are critical because they use beamforming gain to construct links with a suitable signal-to-noise ratio (SNR) to extend the communication range and overcome path losses. Beamforming technology, in general, employs an antenna array to perform spatial filtering in order to capture or radiate a signal in specific directions over its aperture based on information received via the Angle-of-Arrival (AoA) method [6][7][8]. As a result, prioritising transmit and/or receive gain over the omnidirectional transmission or reception can significantly improve both base and mobile stations [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…However, sound location only requires a person to make a sound, and when the microphone receives the sound signal, it can perform an estimate of the position. In recent years, many studies have proposed using acoustics to achieve the effect of localization, namely acoustic source localization [13][14][15][16][17][18][19]. The advantages of acoustic localization are penetrating power, simple structure, and low cost.…”
Section: Introductionmentioning
confidence: 99%
“…M-MIMO technology, the size of the received or measured data is expected to be massive and, therefore, the strategy for data sampling plays a significant role in the direction-finding system's performance [5]. Hence, the means of obtaining such data sets from the measured matrix in the signal processing stage is an interesting problem: this can be tackled, based on the Extreme Value Theory (EVT) [6].…”
mentioning
confidence: 99%
“…Though it has low complexity and provides good estimation precision under highly coherent signals and small numbers of data measurement conditions, its performance depends mainly on the array aperture size. Alternatively, for complexity reduction purposes, it is possible to utilize L columns from the obtained CM to form such a projection matrix instead of using the complete CM or decomposing it [5]. It has been demonstrated that any increase in the number of sampled columns has a positive impact on the effectiveness of the projection matrix construction through improving the estimation accuracy and Probability of Successful Detection (PSD) [33], [34].…”
mentioning
confidence: 99%